Editorial - Bozalek, Vivienne; Gachago, Daniela (Critical Studies in Teaching and Learning, 2023)
As the managing editor and editor-in-chief of the journal Critical Studies in Teaching and Learning (CRiSTaL), we have, for some time, been eager to get the editorial board together to engage with the concept of ‘critical’, since, for us, it is such a central focus for the journal. Because the notion of criticality means different things to different people, we noticed that as editors, we sometimes struggle to share our own understanding of criticality both with each other and with the authors who submit articles to us. We thus decided to send out a call for papers for a special issue on criticality where we - as editorial team - would have an opportunity to unpack our understandings of criticality within our fields and disciplines. This special issue includes papers from some of the editorial board members who responded to this call. As the managing editor and editor-in-chief, we are often sent manuscripts from authors whose work on first perusal we have to reject because there is no indication of criticality which is required from submissions to the journal.